Experimental verification of the development of college students’ value professional orientation - Demianiuk, Viktor; Pelekh, Yurii (Journal of Education, Health and Sport, 2019)
The purpose of the paper is to reveal the peculiarities of the formation of value professional orientation of college students in specialty “Accountant”. The study was conducted to confirm the authors’ concept intended to facilitate a more effective assimilation of the system of human and professional values by accountant students from the experimental group. Based on this concept, the students from the experimental group were supposed to demonstrate better learning results than students in the regular group. For this purpose, the authors’ courses "Philosophical and Historical Context for the Development of Axiology" and a special course "Ethics Code for Professional Accountants" were used to distinguish the training program. By applying the authors’ methodology, special pedagogical conditions and models, we succeeded in raising the level of value professional orientation of future accountants and in achieving better learning results. The scientific approach, which is based on the comparison of techniques for the development of students’ value sphere to enhance the educational attainment of college students, had not previously been applied.